Implementasi Alat Peraga Edukasi Piplas (Pipet Plastik) untuk Meningkatkan Pemahaman IPA pada Siswa di SMP Negeri 1 Gangga - Nurkhasanah, Siti (Jurnal Paedagogy, 2020)
The study aims to increase the understanding of gene concepts and inheritance by providing a more concrete representation of the genes. The design of this research uses the quantitative approach of experimentation. Subjects and objects of study are students of grade IX-5 SMP Negeri 1 Gangga, amounting to 29 not one person until a total of 28 people. This Piplas educational tool is very simple because it only makes use of plastic pipettes used by ice-drinking students. Usually plastic pipettes are used for crafting, but are used to provide a concrete representation of the genes. The results showed that most students are easier to understand the concept of genes, capable of making crosses easily so as to improve learning outcomes. Tests were given before learning obtained an average value of 30.79 and after learning obtained an average value of 69.4 an increase of 125.4%.